Morocco’s Subsidized Health Insurance Regime for the Poor and Vulnerable Population : Achievements and Challenges - Chen, Dorothee (World Bank, Washington, DC, 2018)
In Morocco, a reform process to establish universal health coverage (UHC) through nonsubsidized and subsidized social health insurance (SHI) was launched in 2002. This case study focuses on the subsidized SHI scheme, régime d’assistance médicale (RAMED). This program, which is Morocco’s flagship social protection and health program and which had the support of the King Mohamed VI, was piloted in 2008 and scaled up to the national level in 2012. As of November 2016, 6.35 million people - 19 percent of the population - had valid RAMED identification cards. RAMED relies on a sophisticated methodology to target poor and vulnerable households, combining proxy means testing and community targeting methods. This case study reviews RAMED’s achievements and identifies potential reforms to address the challenges RAMED is facing. After presenting details of the health financing and delivery systems and an overview of public health care, the case study reviews RAMED’s institutional arrangements, poverty targeting, enrolment and identification mechanisms, benefits package, and information environment system. The study concludes with a discussion of potential areas of improvements.